Efficacy and safety of the Janus kinase 1 inhibitor PF‐04965842 in patients with moderate‐to‐severe psoriasis: phase II, randomized, double‐blind, placebo‐controlled study. (6th March 2018) - Schmieder, G.J.; Draelos, Z.D.; Pariser, D.M.; Banfield, C.; Cox, L.; Hodge, M.; Kieras, E.; Parsons‐Rich, D.; Menon, S.; Salganik, M.; Page, K.; Peeva, E.
Summary: Background: PF‐04965842 is an oral Janus kinase 1 inhibitor being investigated for the treatment of plaque psoriasis. Objectives: To evaluate the efficacy, safety and tolerability of PF‐04965842 in patients with moderate‐to‐severe plaque psoriasis. Methods: Patients in this phase II, placebo‐controlled study (NCT02201524) were randomized to receive placebo, 200 mg once daily (OD), 400 mg OD or 200 mg twice daily (TD) PF‐04965842 for 4 weeks. The primary endpoint was change from baseline in Psoriasis Area Severity Index (PASI) at week 4. Study enrolment was discontinued on 25 June 2015 due to changes in the sponsor's development priorities. Results: Fifty‐nine patients were randomized and received at least one dose of PF‐04965842 or placebo. The estimated treatment effect (active –placebo PASI change from baseline) and 90% confidence interval at week 4 was −5·1 (−9·2 to −1·0), −5·6 (−9·6 to −1·6) and −10·0 (−14·2 to −5·8) for the 200 mg OD, 400 mg OD and 200 mg TD groups, respectively. At week 4, the proportion of patients achieving PASI 75 was 17% for the placebo and 200 mg OD groups, 50% for the 400 mg OD group and 60% for the 200 mg TD group. There were more abnormal laboratory test results of clinical interest (low neutrophil, reticulocyte and platelet counts) in the 200 mg TD group compared with the OD treatment groups. No serious infections or bleeding events related to neutropenia or thrombocytopenia, respectively, were reported. Conclusions: These results suggest that treatment with PF‐04965842 improves symptoms and is well tolerated in patients with moderate‐to‐severe psoriasis. Abstract : What's already known about this topic? Proinflammatory cytokines play a key role in plaque psoriasis. There remains an unmet need for effective and well‐tolerated new therapies for plaque psoriasis because treatment failures can occur with currently available treatments. Janus kinase inhibitors are being investigated for the treatment of inflammatory diseases. What does this study add? Results from this phase II, randomized study suggest that treatment with 200 mg once daily (OD), 400 mg OD and 200 mg twice daily doses of PF‐04965842 improves psoriasis symptoms and is well tolerated in patients with moderate‐to‐severe psoriasis. Respond to this article